Mencari, Menemukan, dan Mengomunikasikan Nilai-nilai Bermain dalam Konteks Pendidikan - Hendar Putranto (Ultimacomm: Jurnal Ilmu Komunikasi, 2010)
Play is an indispensable dimension to successful and integral education. Nevertheless, our culture today tends to neglect play as its constitutive element. There are several reasons behind the negligence of play within our educational realm. This writing would refresh the way we think about play its anthropological and philosophical signifance, and its important role in shaping child’s character in positive and substantial ways before embarking into mature years as an adult. We also look at why and how we should communicate values of play to students (within the context of the classroom) and to larger audience (within the context of daily life). Some examples taken as role models of play in local context (Laskar Pelangi) and in educational realm would strengthen the main argument of the writing. Kata Kunci: media communication, intellectual characters, education